Untangling teacher burnout: a network analysis of demands, resources, and out-of-field teaching challenges in rural China - Ming Huo (Frontiers in Public Health)
IntroductionTeacher burnout poses a significant threat to the sustainability of rural education. However, the effect of out-of-field teaching as a job demand remains understudied. This study applies the Job Demands-Resources (JD-R) model to explore how job demands, job resources, and personal resources interact with burnout among rural teachers.MethodsWe conducted a network analysis on survey data from 2,475 English teachers in rural China, including 2,119 in-field and 356 out-of-field teachers, to examine the relationships between JD-R variables and burnout dimensions.ResultsEmotional exhaustion emerged as the central burnout dimension, with workload stress acting as the primary bridge connecting JD-R variables to burnout. Job satisfaction showed strong negative bridge effects, indicating its association with lower depersonalization. The network structure and strength were similar for in-field and out-of-field teachers, suggesting that out-of-field teaching may not be directly related to teacher burnout.DiscussionThese findings suggest that interventions targeting workload reduction and enhancing professional identity and recognition could alleviate burnout and support the sustainability of rural education in China.